Parental Levels of Satisfaction about the Efforts Made by Teachers in Adapting the Curriculum for Students with Moderate Physical Impairment Studying at the Primary Level in Punjab - Nawaz, Hamayoun Shah; Fazil, Hina (Annals of Human and Social Sciences, 2023)
Parental satisfaction specify in this study, the degree to which parents are satisfied about the efforts made by teachers in adapting the curriculum for students with Moderate Physical Impairment (MPI). In this study, researchers used a quantitative research approach and employed a descriptive research design. A survey method was used with a self-made instrument to collect data from purposively selected 179 parents. The value of the Coefficient Alpha was .907. The survey focused on nine areas: size, time, level of support, input, difficulty level, output, participation, alternate goal, and substitute curriculum. Descriptive and inferential statistics was employed to analyse the data. The results revealed that overall parents had a low level of satisfaction with the efforts made by teachers in adapting the curriculum. In most of the areas of curriculum adaptations, significant differences were not found in parental levels of satisfaction based on gender and residential locality. This study recommends that teachers need professional training to implement adaptations in the classroom.